2020
DOI: 10.21203/rs.3.rs-126159/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Identification, Expression and Potential Function Analysis of the ERF and DREB Subfamily Members in Tomato

Abstract: Background: APETALA2/ethylene responsive factors (AP2/ERFs) are unique regulators found in the plant kingdom that are involved in all life activity processes, including flowering, fruit ripening, floral meristem growth, and defense responses. In tomato (Solanum lycopersicum), there are 60 DREB and 80 ERF subfamily members, however, their functionality remains poorly understood.Results: In this work, the AP2 domain conserved amino acid sequences of 68 ERF proteins from 20 plant species were compared and a Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 71 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Zhang et al (2010) found that JERF1, a tomato ERF protein, significantly enhanced drought tolerance of transgenic rice through increasing the synthesis of the osmolyte proline. Besides, An et al (2020) found that MdERF38, an apple ERF protein, promoted anthocyanin biosynthesis in response to drought stress. In rice, OsERF115/AP2EREBP110 enhance drought tolerance by elevating the expression level of a proline biosynthesis P5CS1 gene (Park S. I. et al, 2021).…”
Section: Erfs Involved In Drought Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang et al (2010) found that JERF1, a tomato ERF protein, significantly enhanced drought tolerance of transgenic rice through increasing the synthesis of the osmolyte proline. Besides, An et al (2020) found that MdERF38, an apple ERF protein, promoted anthocyanin biosynthesis in response to drought stress. In rice, OsERF115/AP2EREBP110 enhance drought tolerance by elevating the expression level of a proline biosynthesis P5CS1 gene (Park S. I. et al, 2021).…”
Section: Erfs Involved In Drought Stressmentioning
confidence: 99%
“…Lv et al (2019) found that overexpression of BpERF13 up-regulated SOD1, SOD3, POD6, POD8, CBF3 and CBF4 genes and down-regulated the accumulation of ROS to resist oxidative stress, thus enhancing the cold tolerance of birch (Betula platyphylla). Hu et al (2020) showed that overexpression of CdERF1 in bermudagrass (Cynodon dactylon) positively regulated cold response by activating cold stress-related genes PODs, CBF2 and LTPs. In transgenic Arabidopsis, heterologous expression Malus baccata MbERF11 contributed to cold stress response probably by promoting the ability to scavenge ROS (Han et al, 2020).…”
Section: Erfs Involved In Cold Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, proteins with the AP2 domain consisting of 14 th V and 19 th E have been more likely characterized as DREBs, but those with an alanine (A)- and aspartate (D)-containing AP2 motif are assigned to ERF proteins. 27 Because the specific AP2 recognizes and binds to the DRE (dehydration-responsive element) cis -regulatory sequence in regulatory networks, such a AP2 domain represents a typical feature for DREB genes. Thus, in this study, we further used the 172 MsDREB -gene datasets for the preliminary analysis of alfalfa plant in response to cold stress.…”
Section: Resultsmentioning
confidence: 99%